Housing and the Creation of Home for Refugees in Western Australia - Fozdar, F.; Hartley, Lisa (Routledge Tailor Francis, 2013)
Safe, appropriate housing is vital for the successful settlement of refugees, since establishing a home is part of the process of redeveloping a sense of ontological security. However humanitarian entrants in Australia have a far greater likelihood of moving multiple times in the early years of settlement and are far less likely to be purchasing their homes compared to other migrants. Using data from interviews, focus groups and a photovoice exercise, positive home-building experiences of refugees are illustrated, while factors leading to negative outcomes are also identified. The more positive story came from the photovoice exercise with images of the remaking of home as a place of connection with others, of personal pride, of comfort and leisure, of family and commensality. Interview and focus group data focused on structural issues including the cost of housing, limited choice in the rental market, lack of public housing, poor quality, negative attitudes of real estate agents, lack of access to services, and complex tenancy procedures which are key factors influencing insecurity of tenure. The effects on refugees’ sense of ontological security are discussed.